Protocolo AGITO: Autocuidado em diabetes tipo 1 para um aplicativo de dispositivo móvel - Fernanda Figueredo Chaves (2019)
Introduction: The study was designed from the need to provide a protocol that can be used through a mobile application as a self-care strategy for adolescents with type 1 diabetes using the emotion approach. Objective: Carry out the elaboration, validation and cultural adequacy of the AGITO protocol in a mobile device application for self-care in type 1 diabetes. Methods: Methodological study, covering two steps: 1st) Integrative Review and 2st) Preparation, content validation and cultural adequacy. The main themes of self-care practices in type 1 diabetes were considered, concerning the aspects: educational, psychosocial and behavioral. In the second stage, 32 health care professionals were invited to participate in the Judges Committee. The final stage comprised two cycles of face-to-face protocol testing with 10 adolescents with type 1 diabetes. Results: These are presented according to each stage. Stage One: In the integrative review 12 articles met the selection criteria. The app features were examined from the glycemic control, insulin therapy, diet, physical activity, emotional approach, and social relationships functions. Second stage: The type 1 diabetes self-care protocol named AGITO was consolidated into six sections, namely: 1- Fasting Blood Glucose; 2- Blood glucose before lunch; 3 - Blood glucose before the afternoon snack, 4 - Blood glucose before dinner; 5 - Blood glucose before bedtime snack; and 6- Emotional health. The agreement between the evaluators and the target population regarding the clarity and relevance of the items was confirmed by the Content Validity Index, which varied from 0.90 to 1.0. The main changes in content adequacy were the inclusion of terms most used in the self-care daily life of adolescents with type 1 diabetes. Conclusion: This study provides the AGITO application protocol with validated content, configuring a component that can be used as a strategy for self-care in type 1 diabetes for adolescents.